Coefficient of hydraulic resistance of capillary friction at low Reynolds numbers - Oleh Selezen; Mark Shliakhov; Roman Orlov (Авіаційно-космічна техніка та технологія, 2023)
Heat transfer pump circuits with liquid or two-phase heat transfer fluids are widely used in thermal management systems in both space and ground applications. These systems play an important role in maintaining the optimal temperature and heat distribution in various processes and devices. Such systems use throttles to ensure efficient distribution of coolant flows through the hydraulic network. It is especially important to ensure the reliability of the system at low coolant consumption. Therefore, a rational approach is to manufacture throttles in the form of capillary segments. Capillary throttles can regulate the flow of coolant with high accuracy, which makes it possible to improve control over the thermal regime of the system. To calculate and determine the characteristics of such throttles, it is important to know the coefficient of hydraulic friction resistance λ, which is used in the Darcy formula. This coefficient depends on various factors, including the geometry of the throttle, physical properties of the heat transfer fluid, and flow conditions. Therefore, the aim of this study was to determine the value of the hydraulic friction resistance coefficient λ. In this work, experiments were performed with the shedding of copper capillaries of different internal diameters (0.8-1.2 mm) in water and isopropyl alcohol. The experiments were carried out in the laminar and transient regions, in the range of Reynolds numbers from 250 to 6050. Conclusions. In the laminar region (Re < 1185), it is recommended to use the Poiseuille formula. In the transitional and turbulent regions (1185 < Re < 6050), it is recommended to use the Blasius formula. The results of the experiments made it possible to obtain data on the value of the hydraulic friction resistance coefficient λ. These data can be used to calculate throttles in similar heat transfer systems. Moreover, the paper provides recommendations on the use of well-known formulas for calculating throttles, which allows engineers and designers to effectively implement these elements in their projects. Thus, the research conducted in this paper has important practical implications for the development and optimization of heat transfer systems in space and terrestrial applications.